Necroptosis in Macrophage Foam Cells Promotes Fat Graft Fibrosis in Mice - Chen, Xihang; Deng, Zilong; Feng, Jingwei; Chang, Qiang; Lu, Feng; Yuan, Yi (Frontiers in Cell and Developmental Biology, 2021)
BABSTRACT Background: Fibrosis is a major grafting-related complication that leads to fat tissue dysfunction. Macrophage-induced inflammation is related to the development of fat tissue fibrosis. Necroptosis is a recently discovered pathway of programmed cell necrosis that results in severe inflammation and subsequent tissue fibrosis. Thus, in this study, we investigated the role of macrophage necroptosis in fat graft fibrosis and the underlying mechanisms. Methods: Fibrosis and necroptosis were investigated in mouse fat tissue before and after grafting. An in vitro “crown-like” structure (CLS) cell culture model was developed by co-culturing RAW 264.7 macrophages with apoptotic adipocytes to reproduce in vivo CLS macrophage-adipocyte interactions. Lipid uptake and necroptosis in CLS macrophages were analyzed using Oil-Red-O staining, western blotting, and immunofluorescence. RAW264.7 macrophages were cultured alone or with apoptotic adipocytes and treated with a necroptosis inhibitor (Nec-1 or GSK872) to explore the paracrine effect of necroptotic CLS macrophages on collagen synthesis in fibroblasts in vitro. Mice were treated with Nec-1 to analyze the effect of blocking necroptosis on fat graft fibrosis. Results: Fibrosis was increased after grafting in fat grafts of mice. Macrophages clustered around apoptotic adipocytes or large oil droplets to form a typical CLS in fibrotic depots. This was accompanied by formation and necroptosis of macrophage foam cells (MFCs) in CLSs. RAW 264.7 macrophages co-cultured with apoptotic adipocytes induced CLS formation in vitro, and lipid accumulation in CLS macrophages resulted in the formation and necroptosis of MFCs. Necroptosis of MFCs altered the expression of collagen I and VI in fibroblasts via a paracrine mechanism involving inflammatory cytokines/chemokines, which was reversed by GSK872 or Nec-1 treatment. Furthermore, treatment with Nec-1 ameliorated fat graft fibrosis in mice. Conclusions: Apoptotic adipocytes induced necroptosis of MFCs, and necroptosis of these cells activated collagen synthesis in fibroblasts via a paracrine mechanism. Inhibition of necroptosis in macrophages is a potential approach to prevent fibrosis in fat grafts.